Canine Descemet Stripping Endothelial Keratoplasty with a Tissue Insertion Device: Technique and Long-Term Outcome - Conan Y. Chen; Steven J. Solar; Daniel S. Lewis; Kali Barnes; Batya G. Wiener; Satya Baliga; Eric Chiang; Tim E. Askew; Allen O. Eghrari; Micki D. Armour (Case Reports in Veterinary Medicine)
Introduction. We describe a case of canine Descemet’s stripping endothelial keratoplasty (DSEK) using an open-source canine tissue delivery device. Case Presentation. We follow the four-year outcomes of a 1.5-year-old Tibetan Terrier who presented with difficulty seeing, diffuse corneal edema, and central corneal thickness of 1400 microns in the left eye. To perform DSEK, a polycarbonate carrier and insertion device was designed for canine corneas that measure up to 15 mm in diameter. The tissue was loaded into the inserter prior to surgery with the endothelium facing inwards and the stroma facing the cartridge wall. From the cartridge, the graft was pulled into the eye using microforceps and an anterior chamber maintainer. We assessed preoperative endothelial cell count, postoperative corneal clearance, and graft adhesion. The donor was a two-year-old Airedale Terrier who died one day prior to surgery, with endothelial cell density of 3149 cells/mm2. One week after DSEK, the cornea began to clear, and pachymetry of the donor and graft total was 1410 microns. This improved to 800 microns at 4 months and continued improving in its clarity at the last postoperative visit 4 years after surgery. Discussion. We demonstrate the feasibility of conducting canine endothelial keratoplasty with a specially designed tissue delivery device and the potential of long-term corneal clearance after DSEK in canine eyes.